Acute function of secreted amyloid precursor protein fragment APPsα in synaptic plasticity - Hick, Meike; Herrmann, Ulrike; Weyer, Sascha W.; Mallm, Jan-Philipp; Tschäpe, Jakob-Andreas; Borgers, Marianne; Mercken, Marc; Roth, Fabian C.; Draguhn, Andreas; Slomianka, Lutz; Wolfer, David P.; Korte, Martin; et al. (Acta neuropathologica, 2015)
The key role of APP in the pathogenesis of Alzheimer disease is well established. However, postnatal lethality of double knockout mice has so far precluded the analysis of the physiological functions of APP and the APLPs in the brain. Previously, APP family proteins have been implicated in synaptic adhesion, and analysis of the neuromuscular junction of constitutive APP/APLP2 mutant mice showed deficits in synaptic morphology and neuromuscular transmission. Here, we generated animals with a conditional APP/APLP2 double knockout (cDKO) in excitatory forebrain neurons using NexCre mice. Electrophysiological recordings of adult NexCre cDKOs indicated a strong synaptic phenotype with pronounced deficits in the induction and maintenance of hippocampal LTP and impairments in paired pulse facilitation, indicating a possible presynaptic deficit. These deficits were also reflected in impairments in nesting behavior and hippocampus-dependent learning and memory tasks, including deficits in Morris water maze and radial maze performance. Moreover, while no gross alterations of brain morphology were detectable in NexCre cDKO mice, quantitative analysis of adult hippocampal CA1 neurons revealed prominent reductions in total neurite length, dendritic branching, reduced spine density and reduced spine head volume. Strikingly, the impairment of LTP could be selectively rescued by acute application of exogenous recombinant APPsα, but not APPsβ, indicating a crucial role for APPsα to support synaptic plasticity of mature hippocampal synapses on a rapid time scale. Collectively, our analysis reveals an essential role of APP family proteins in excitatory principal neurons for mediating normal dendritic architecture, spine density and morphology, synaptic plasticity and cognition.
Online veröffentlicht: 29. November 2014
Gesehen am 31.08.2020